Small-scale protocols to characterize mitochondrial Complex V activity and assembly in peripheral blood mononuclear cells - Kai-Yin Chau; Jan-Willem Taanman; Anthony H.V. Schapira (PLoS ONE, 2025)
Complex V of the mitochondrial oxidative phosphorylation system is an ATP synthase that plays a pivotal role in the cell’s energy transduction. Mutations in genes encoding the multiple protein subunits that constitute complex V cause severe metabolic and neurodegenerative diseases. We present here three complementary assays to assess Complex V activity and assembly in peripheral blood mononuclear cells (PBMCs). The assays involve spectrophotometric and in-gel activity measurements, cytochemical assessment of the mitochondrial transmembrane electrochemical gradient (∆Ѱm) to determine if the enzyme acts forward as an ATP synthase or in reverse as an ATPase, and western blot analysis of clear native gels to evaluate Complex V assembly. The whole process can be performed with 2 × 106 PBMCs isolated from ~2 ml of blood. Our study suggests that PBMCs can serve as a platform for small-scale, minimally invasive investigations of patients suspected of Complex V deficiency or in biomarker research of mitochondrial function.